An overview of the preclinical and clinical studies of the effects of tumor treating fields on malignant glioma cells - Bądziul, Dorota; Banaś-Ząbczyk, Agnieszka; Tabarkiewicz, Jacek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Anaplastic astrocytoma (AA, WHO grade III) and glioblastoma multiforme (GBM, WHO grade IV) are malignant tumors of the brain. The average survival time of patients with GMB is approximately one year and two years in the case of anaplastic astrocytoma with standard therapy based on surgical tumor resection followed by chemotherapy or radiotherapy. High invasiveness of gliomas, the ability of rapid division and so-called diffusive infiltration of tumor cells into normal brain tissue, which prevents complete surgical removal, are hallmarks of theses tumors. Therefore, new specific therapies for eliminating cancer cells are needed to treat this tumors. Recently, it has been demonstrated that alternating electric field, also known as tumor treating fields (TTFields) has a unique mechanism of destroying glioma cells. TTFields applies electromagnetic energy frequency-dependent and intensitydependent and disrupts cancer cell replication as they undergo mitosis. Futhermore, TTFields turn out to act comparably to conventional chemotherapeutics, lacking numerous side adverse associated with chemotherapy. The authors provide an up-todate review of the mechanism of action as well as preclinical and clinical data on TTFields.
Keywords: anaplastic astrocytoma; glioblastoma multiforme; brain tumor; tumor treating fields; tumor therapy